An invitation to murder eaudiobook - Dobbs, Leighann (Lady Katherine Regency Mystery, 2018)
To stop a high-society killer, she'll have to play matchmaker one last time . . . Lady Katherine would rather chase clues than suitors. Her reputation as a matchmaker could give her the cover she needs to follow in her detective father's footsteps. If she catches the Pink Ribbon Killer before he strikes again, she'll win her dowry and her independence in the process . . . One look through the exclusive Northbrooke estate house party doubles her suspect list. With the help of her trusty maid and her precocious pug, Katherine risks it all to unmask the killer. But is winning her freedom worth putting another debutante in mortal danger?